A Review of Riverbed Extraction and its Effects on Aquatic Environment with Special Reference to Tinau River, Nepal - Dahal, Khet Raj; Sharma, Subodh; Sharma, Chhatra Mani (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Rivers not only maintain the ecological balance but also generate resources. Fishes and riverbed materials such as sand, cobble, pebble, boulders, etc. are the sources of income from natural rivers; and these are the important resources in the construction industry. There exist very few studies on the effects of riverbed extraction in the rivers like Tinau. The lack of generic hydrological and climatic data in the river catchment leads to the lack of knowhow regarding the hydrological behavior of the river basin and its consequences over time. This study is the outcome of the literature review on riverbed extraction and its effects on the aquatic environment particularly in the Tinau River. Riverbed extraction can cause many effects on the environment. But this paper mainly focuses on the effects of riverbed extraction on the hydraulic structures, ground water, river morphology, cost externalization, fish species and fisheries for livelihood. DOI: http://dx.doi.org/10.3126/hn.v11i0.7163 Hydro Nepal Vol.11 2011 pp.49-56